Charity of nations - "Wall, David" (New York, 1973)
This volume is the second of the Basic Books series on political economy of international relations. The series is signed to fill a serious gap in the modern, conventional litera on international relations-a gap which exists between the ciplines of economics and political science. For the most E economists writing about international economics tend to igr the political aspects of their subject. Struggles for power conflicts of interest are either ignored or assumed away, or they are dismissed as "irrational" aberrations in the behavic economic man. Conversely, most political scientists writing al international politics tend to ignore the economic aspects of subject. Considerations of welfare and resource allocation ha ever seem to figure importantly in any of their discussions. a few lonely scholars seem prepared to combine and integ both aspects of international relations within a single analy framework.
Keywords: Economics